How bacterial cells keep ribonucleases under control. Issue 3 (14th April 2015) - Deutscher, Murray P.
Abstract : Ribonucleases (RNases) play an essential role in essentially every aspect of RNA metabolism, but they also can be destructive enzymes that need to be regulated to avoid unwanted degradation of RNA molecules. As a consequence, cells have evolved multiple strategies to protect RNAs against RNase action. They also utilize a variety of mechanisms to regulate the RNases themselves. These include post-transcriptional regulation, post-translational modification, trans-acting inhibitors, cellular localization, as well as others that are less well studied. In this review, I will briefly discuss how RNA molecules are protected and then examine in detail our current understanding of the mechanisms known to regulate individual RNases. Abstract : Cells employ a variety of strategies to regulate their complement of ribonucleases to ensure sufficient activity to meet their metabolic requirements and, at the same time, to avoid indiscriminate destruction of important RNA molecules. Abstract :